Influence of processing conditions on the phase transition and ferroelectric properties of Pb(Zn1/3Nb2/3)O 3-Pb(Zr1/2Ti1/2)O3 ceramics - Vittayakorn N. (2014)
Ceramics solid solutions within the binary system of xPb(Zn 1/3Nb2/3)O3-(1-x)Pb(Zr1/2Ti 1/2)O3 with x=0.1-0.5 were synthesized via the mixed oxide method and the columbite method. Phase development of calcined powders and the crystal structure of sintered ceramics were analyzed by X-ray diffraction. Ferroelectric properties were measured to elucidate the phase transformation and identify the impact of the processing conditions. It is shown that there was no significant difference in Pr across the composition range. However, the coercive field Ec was shown to exhibit a strong compositional dependence. Compared with ceramics prepared by the columbite method, ceramics prepared by the mixed oxide method showed a lower remanent polarization P r and a higher coercive field Ec. In addition, both X-ray diffraction and ferroelectric measurements indicated a phase transformation from a tetragonal to a pseudo-cubic rhombohedral phase when the fraction of Pb(Zn1/3Nb2/3)O3 (PZN) was increased. The morphotropic phase boundary (MPB) is located between x = 0.2 and 0.3 according to observations made on ceramics prepared with the columbite method. However, this transformation was obscured in the ceramics prepared with the mixed oxide method. It is proposed that compositional heterogeneities were responsible for these experimental investigations. © 2004 Elsevier B.V. All rights reserved.